Genetic Diversity in Some Sesame (Sesamum indicum L.) Accessions Detected by Agro-morphological Characters and RAPD Markers* (University of Khartoum Journal of Agricultural Sciences, 2023)
Agro-morphological and Randomly Amplified PolymorphicDNA (RAPD) markers were used to determine the diversity andrelationships among 25 accessions of sesame from Sudan. Data on 16agro-morphological characters were collected from a field experiment,carried out at Shambat for three consecutive seasons (2006-2008) andsubjected to the procedure of cluster analysis. The results showed thatcluster analysis, based on Euclidean distance, of the agro-morphologicalcharacters grouped the 25 sesame accessions into seven clusters.Application of RAPD markers generated 48 bands with a 97.9%polymorphism. A dendrogram constructed from the RAPD data classifiedthe 25 sesame accessions into eight major clusters. It was concluded thatfor efficient estimation of genetic diversity and interrelationships amongsesame accessions, information obtained from both agro-morphologicalcharacters and RAPD should be combined.
Keywords: Sesame; genetic diversity; agro-morphological characters; RAPD